2014
DOI: 10.1002/2014gl060826
|View full text |Cite
|
Sign up to set email alerts
|

The importance of spring atmospheric conditions for predictions of the Arctic summer sea ice extent

Abstract: Key Points:• Arctic spring atmosphere can be used for prediction of September sea ice • Simple models using spring atmospheric predictors provide high predictive skills • The skills of these simple models are similar to those of complex models Abstract Recent studies have shown that atmospheric processes in spring play an important role for the initiation of the summer ice melt and therefore may strongly influence the September sea ice concentration (SSIC). Here a simple statistical regression model based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 49 publications
3
68
0
5
Order By: Relevance
“…Figure 8 displays the relationship between the changes in the sea ice melting and the associated atmospheric variables in the APS before and after 2002 for each month from April to November. According to previous studies (Kapsch et al 2013(Kapsch et al , 2014, positive downward longwave radiation anomalies in March and April can control the summer/autumn sea ice by affecting the timing of the onset of the melting season. We also find that the moisture flux convergence and downward longwave radiation are increased after 2002 in April and May in addition to summer, which is an additional contributor to reduced summer SIA after 2002 by affecting the onset of sea ice melting.…”
Section: B Analysis Of Heat and Moisture Fluxmentioning
confidence: 83%
See 2 more Smart Citations
“…Figure 8 displays the relationship between the changes in the sea ice melting and the associated atmospheric variables in the APS before and after 2002 for each month from April to November. According to previous studies (Kapsch et al 2013(Kapsch et al , 2014, positive downward longwave radiation anomalies in March and April can control the summer/autumn sea ice by affecting the timing of the onset of the melting season. We also find that the moisture flux convergence and downward longwave radiation are increased after 2002 in April and May in addition to summer, which is an additional contributor to reduced summer SIA after 2002 by affecting the onset of sea ice melting.…”
Section: B Analysis Of Heat and Moisture Fluxmentioning
confidence: 83%
“…Both ERAInterim and ERA-20C have a horizontal resolution of 0.758 3 0.758. Kapsch et al (2013) found ERA-Interim to be the most credible reanalysis for Arctic climate.…”
Section: A Observational Datamentioning
confidence: 96%
See 1 more Smart Citation
“…Arctic sea ice forecasts for seasonal-to-annual time scales are often based on statistical methods (e.g., Lindsay et al 2008;Kapsch et al 2013). With the fastchanging Arctic climate, however, the historical records on which the statistical relations are based are not necessarily valid for the current climate state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by Kapsch et al (2013Kapsch et al ( , 2014 also investigated the role of spring atmospheric forcing on sea ice variability. They showed a clear connection between anomalies in spring L↓ and S↓, and September sea ice anomalies in a large part of the Arctic ocean.…”
Section: Discussionmentioning
confidence: 99%